2019
DOI: 10.3390/nu11092200
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Fat Consumption and the Risk of Metabolic Syndrome: An Examination of the Saturated Fatty Acids in Dairy

Abstract: Lifestyle is a key modifiable risk factor involved in the manifestation of metabolic syndrome and, in particular, diet plays a pivotal role in its prevention and development. Current dietary guidelines discourage the consumption of saturated fat and dietary sources rich in saturated fat, such as dairy products, despite data suggesting that full-fat dairy consumption is protective against metabolic syndrome. This narrative review assessed the recent epidemiological and clinical research that examined the consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 119 publications
(209 reference statements)
2
52
0
Order By: Relevance
“…A systematic review by Telle-Hansen et al (84) of 37 RCT suggests minor or no effects of dietary fat intake on inflammatory markers in overweight/obese subjects. Emerging evidence indicates that dairy product consumption is linked to lower risk for CVD and metabolic syndrome, and the lack of detrimental effects from intake of saturated fat can be attributed to the heterogeneity of saturated fatty acids unique to the dairy food matrix (85). Specifically, a systematic review by Drouin-Chartier et al (34) concluded that neither total dairy product nor cheese consumption was associated with higher risk for coronary artery disease or CVD, and total dairy product and cheese intake were associated with lower stroke risk.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Telle-Hansen et al (84) of 37 RCT suggests minor or no effects of dietary fat intake on inflammatory markers in overweight/obese subjects. Emerging evidence indicates that dairy product consumption is linked to lower risk for CVD and metabolic syndrome, and the lack of detrimental effects from intake of saturated fat can be attributed to the heterogeneity of saturated fatty acids unique to the dairy food matrix (85). Specifically, a systematic review by Drouin-Chartier et al (34) concluded that neither total dairy product nor cheese consumption was associated with higher risk for coronary artery disease or CVD, and total dairy product and cheese intake were associated with lower stroke risk.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors, especially hypercaloric diets, are the main contributors to the aetiology of MtS [28]. Chronic consumption of HFD induces overweight along with metabolic and cardiovascular alterations, such as insulin resistance, dyslipidemia or hypertension, among others, being all of these symptoms of the MtS [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The national dietary guidelines might treat SFA contained in the diet as a single group of nutrients [30].…”
Section: Discussionmentioning
confidence: 99%